A mapping of the positions of adults in Toulouse, France, regarding induced abortion. (June 2015) - Muñoz Sastre, Maria Teresa; Petitfils, Charlotte; Sorum, Paul Clay; Mullet, Etienne
Abstract: Background Are people's views on abortion as polarised as is suggested by the 'marches for life' that regularly take place in Paris and other capitals? Objective To map French people's positions regarding the acceptability of induced abortion. Methods One hundred and fifty-nine participants were presented with stories composed according to a three within-subject design: Reason for abortion (e.g., the woman's life is endangered) × Gestational age × Woman's age. They assessed the extent to which abortion would be, in each case, an acceptable medical/surgical procedure. Results Five qualitatively different positions were identified: (i) always acceptable, irrespective of circumstances (31% of the sample), (ii) strictly depends on the reason for abortion (27%), (iii) legalist (23%), (iv) depends on the reason and on the gestational age (18%), and (v) always unacceptable (1%). Conclusions Only one-fifth of the participants agreed with the part of the French law that permits abortion on request when gestational age does not exceed ten weeks. The others disagreed either because they thought that abortion on demand should never be permitted or because they thought that the age limit should be extended. This divide in people's opinions guarantees that the debate over induced abortions will continue. Chinese Abstract 摘要 背景 在法国巴黎和其他重要城市，常常发生"反对流产"的示威游行，即所谓的为生命而示威。那么人们对于流产的态度是否像游行的人所说的那样呈现两极分化呢？ 目的 了解法国人对人工流产的态度和立场。 方法 159人参与了这项调查。在调查中，会告知她们一些与流产有关的事项。在这些事项中，必然会涉及三个重要的内容，包括妇女流产的理由（比如可能是继续妊娠会使妇女的生命受到威胁）以及流产的胎龄和妇女的年龄。他们将根据自己的观点来判断到何种程度故事里的药物流产或手术流产是可以接受的。 结果 通过调查发现五种对于人工流产不同的态度：1）总是可以接受，不论什么情况下（占调查人数的31%）；2）严格根据流产的理由（占调查人数的27%）；3）依据法律（23%）；4）根据流产的理由和孕周来定（18%）；以及5）总是不可接受。 结论 只有五分之一的被调查者同意法国法律关于允许不超过10周的妊娠的流产的规定。其他的人有的是因为不同意流产合法化，有的是因为还希望法律的规定在孕龄的限制上应该再放宽一些，他们目前都是不同意这项规定的。这种观点的分歧，必然导致针对流产的争论还将继续下去。